2002
DOI: 10.1080/026404102321011760
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics of successful mountain bikers and professional road cyclists

Abstract: The aims of this study were to compare the physiological and anthropometric characteristics of successful mountain bikers and professional road cyclists and to re-examine the power-to-weight characteristics of internationally competitive mountain bikers. Internationally competitive cyclists (seven mountain bikers and seven road cyclists) completed the following tests: anthropometric measurements, an incremental cycle ergometer test and a 30 min laboratory time-trial. The mountain bikers were lighter (65.3+/-6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
4
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 27 publications
9
64
4
6
Order By: Relevance
“…These data support previous suggestions that XCO-MTB is highly reliant on aerobic 215 capacities relative to body mass (6,11). Separately, while the 60 s, 240 s and 600 s efforts 216 were able to discriminate between the two groups, the shorter duration efforts (5 s, 15 s and 217 30 s) did not.…”
Section: Statistical Analyses 141supporting
confidence: 76%
See 2 more Smart Citations
“…These data support previous suggestions that XCO-MTB is highly reliant on aerobic 215 capacities relative to body mass (6,11). Separately, while the 60 s, 240 s and 600 s efforts 216 were able to discriminate between the two groups, the shorter duration efforts (5 s, 15 s and 217 30 s) did not.…”
Section: Statistical Analyses 141supporting
confidence: 76%
“…These investigations have reported that XCO-MTB athletes possess high 37 relative o 2 max values (e.g. national level riders: 65-75 ml·kg -1 ·min -1 ; international riders: 38 75-86 ml·kg -1 ·min -1 ) (2,5,6,8,9,11,17,19). Further, elite XCO-MTB cyclists have 39 demonstrated high maximal aerobic cycling power outputs relative to body mass (6-6.5W·kg -40 well as an intermittent protocol that consisted of five Wingate tests at 50% of single Wingate 46 load with 30 s rest between each effort to compare against XCO-MTB performance.…”
Section: Introduction 23mentioning
confidence: 99%
See 1 more Smart Citation
“…Asimismo, Martínez et al, (1993) determinaron las características antropométricas de 58 ciclistas de competición y encontraron que los ciclistas pesaban 69.6 kg, y tenían una estatura de 173.2 cm, valores que, como se mencionó previamente, son semejantes a la demostrada en ciclistas élite costarricenses. En relación con los análisis realizados según el tipo de prueba, en el presente estudio se demostró que no existe diferencia significativa en las variables antropométricas medidas entre ciclistas que practican solamente ruta y aquellos que practican ruta y MTB de manera conjunta, aunque tomando en cuenta las características del MTB mencionadas por algunos autores (Impellizzeri y Marcora, 2007;Lee et al, 2002), como por ejemplo el tipo de terreno en el que se incluyen ascensos y descensos, senderos de tierra y senderos entre la montaña y el campo, así como el mayor peso de la bicicleta (Impellizzeri y Marcora, 2007), se consideró que podrían existir diferencias bien marcadas en el perfil antropométrico de los ciclistas que realizaban únicamente ruta respecto a los ciclistas que realizaban ruta en combinación con MTB.…”
Section: Discussionunclassified
“…In mountain bike races, body mass seems to be of importance (5,6), since mountain bikers are lighter and leaner compared to road cyclists (6). In mountain-bikers in a cross-country race, total rider mass correlates strongly to average course speed (7) and according to Impellizzeri et al (8), body mass is important for mountain bike performances.…”
Section: Introductionmentioning
confidence: 99%